Return Saham Sebagai Respon Dari Perubahan Tarif PPh Badan Dengan Liabilitas Pajak Tangguhan Sebagai Variabel Intervening - Sonya Enda Natasha S Pandia; Evi Juita Wailan’An (Jurnal Wira Ekonomi Mikroskil, 2023)
This research aims to determine and analyze the affect of changes in company tax rate on Stock Return using deferred tax expense as intervening variable at Property, Real Estate and Construction Companies listed in Indonesia Stock Exchange period 2018-2021. The population in this research amounted to 64 companies.The sampling method used purposive sampling method and obtained 13 sample. The data analysis technique used is quantitative analysis using the classic assumption test and path analysis with the IBM SPSS 25. The result of analysis shows that simultaneously changes in company tax rate no significant effect on deferred tax expense. Partially, changes in company tax rate no significant effect on deferred tax expense. While changes in company tax rate and using deferred tax expense rate no significant effect on stock return. Partially changes in company tax rate and using deferred tax expense rate no significant effect on stock return. The results of the track analysis show that the existence of deferred tax expense rate variables is able to intervening influence of deferred tax expense to stock return.